Early Detection Efforts in Preventing Conflicts Between Silat Colleges by Unit 3 Satintelkam Madiun Police - Putra, Nando Trianugrah (Police Studies Review, 2024)
The Madiun District is known for its abundance of martial arts schools, posing a challenge for relevant agencies, particularly the Indonesian National Police (Polri), in maintaining security and order. Inter-school conflicts within the martial arts community are a primary concern that requires early detection for prevention. This research applies Management Theory and Cooperation Theory in its analysis, utilizing a qualitative approach and field research methods. The findings indicate that Unit 3 of the Intelkam Division of the Madiun District Police is effective in early detection efforts regarding conflicts among martial arts schools, through intelligence gathering from PSHT and Forkopinda. The success of early detection is influenced by human resources, budget, facilities, infrastructure, and cross-sector cooperation. However, challenges persist from martial arts figures who provoke their members, as well as individuals engaging in non-cooperative actions. The research concludes that Unit 3 of the Intelkam Division of the Madiun District Police has successfully created a conducive security situation, yet challenges remain from martial arts figures provoking their members and internal obstacles such as human resources, budget, and methods used needing to be addressed.